Commitment to the Sustainability of Students within a Responsible Management Education - Okręglicka, Małgorzata (European Journal of Sustainable Development, 2018)
Higher education has always responded to the social needs. Universities can play a critical role in the process of social change that relies on educating new generations of leaders and citizens. Higher education shapes the attitudes of many future managers, decision makers, planners, and educators. It has the potential to prepare students and increase information and knowledge in order to move towards a sustainable future. This is why higher education should be involved in implementing the programs of education for sustainable development. The main aim of the paper is the diagnosis of the current student commitment to the sustainability developed by higher education system and its influence on intention to apply the principles of sustainable development in the future. Tools of research included the literature review and questionnaire. The hypotheses are empirically tested with survey data obtained from Polish students of management. The descriptive statistics and correlation analysis will be used in empirical data analysis to achieve the paper goal. By this diagnosis the recommendations for improving responsible management education could be formulated. As a result, students could obtain a high degree of involvement, increasing awareness on their role in society and need for applying the principles of sustainable development, especially taking care of the environment and acting as a responsible member of society. Keywords: sustainability, responsible management education, attitudes, education system, management